Short Note on Sal Heartwood Borer, Hoplocerambyx spinicornis Newn. (Cerambycidae) Epidemic in the Thano Sal Forests Dehra Dun Division - Chatterjee, P. N.; Thapa, R. S. (Indian Forester, 1970)
no abstract